Public Opinion Towards Gene Drive as a Pest Control Approach for Biodiversity Conservation and the Association of Underlying Worldviews. Issue 7 (2nd October 2020) - MacDonald, Edith A.; Balanovic, Jovana; Edwards, Eric D.; Abrahamse, Wokje; Frame, Bob; Greenaway, Alison; Kannemeyer, Robyn; Kirk, Nick; Medvecky, Fabien; Milfont, Taciano L.; Russell, James C.; Tompkins, Daniel M.
ABSTRACT: Synthetic gene drive approaches are nascent technologies with potential applicability for pest control for conservation purposes. Responsible science mandates that society be engaged in a dialogue over new technology, particularly where there exist global ramifications as with gene drive. We hypothesize that public attitudes towards gene drive are not formed on scientific knowledge or demographics alone, but are heavily influenced by underlying worldviews, which encapsulate a broad and interactive system of attitudes, beliefs, and values. To test this, we conducted a national survey in New Zealand ( n = 8199) and found that respondents clustered into four distinct segments with underlying worldviews, better able to explain attitudes toward gene drive than either the participants' scientific knowledge or other explanatory factors such demographics, political ideology or religiosity. We found that the use of gene drive for biodiversity conservation currently has moderate (32%) levels of support in New Zealand but that varied substantially across the four segments. Should gene drive become a technically viable approach for pest control, understanding the worldviews that shape public decision-making can guide a more empathetic engagement process and empower society to participate in informed decision-making about if and how gene drive should be used for conservation purposes.